Inverse colloidal crystal membranes: formation, surface modification and applications - Wang, Xinying, author; Wickramasinghe, Sumith Ranil, advisor; Husson, Scott Michael, committee member; Bailey, Travis Slade, committee member; Qian, Xianghong, committee member (Colorado State University. Libraries, 2010)
Inverse colloidal crystal (ICC) membranes have many advantages, such as highly uniform pore size, fully interconnected pores, and high porosity, over commercially available porous membranes as a selective barrier for ultrafiltration and microfiltration. However, making an ICC membrane which is applicable in separations using reported ICC membrane formation methods has been still not successful yet. We describe here a new ICC membrane formation method, vertical cell (VC) assembly method, to make ICC separation membranes in a simple, low-cost way. The VC assembly method is a versatile colloidal crystal assembly method which is specifically designed for making ICC membranes. Formation of colloidal crystal films(CCF), which is the first step in formation of the inverse colloidal crystal membrane, to large extent determines how good the final membrane properties. The vertical cell assembly method is described that yields CCFs with surface areas up to 5 cm2 and thicknesses up to 100 μm. The thickness of the CCF can also be easily controlled by the spacer which is used. Based on the new ICC membrane formation method, the ICC membranes have been fabricated with a variation of pore-sizes and thicknesses. The membrane casting cell facilitates easy variation of membrane thickness. The membrane pore size is varied by changing the diameter of the silica spheres used to prepare the colloidal crystal template. By changing the composition of the reactive monomer solution, the ICC membranes have been fabricated with different hydrophobicities. Following synthesis, the ICC membranes were tested in a commercially available stirred cell. Particle fractionation was studied in normal flow filtration experiments. The membrane produced from 835 nm particles and 100 μm spacer gives a good passage for 60 nm particles in 60-835 nm bidisperse particle suspension while gives poor passage for the same size paritcles in 60-440 nm bidisperse particle suspension. Fabrication of a UF membrane requires a much smaller pore size. However, for making the ICC membranes with pore size in UF range, it is hard to make them just relying on using small SiO2 particles. This would lead to poor membrane mechanical strength. Here, I described a way to reduce the ICC membrane pore size by growing a uniform poly (poly ethylene glycol methacrylate) (PPEGMA) nano-layer from the membrane surface using surface initiated atom transfer radical polymerization. There are two purposes for the surface modification. One is to control membrane pore size. The other is to improve the membrane surface hydrophobicity. The grafted membranes were characterized with SEM, XPS, ATR-FTIR and water contact angle measurement. Dextran rejection test was conducted on the modified membrane with modification time of 3hr. The rejection rate was obtained for dextran with Mw from 1 kDa through 2000 kDa. The tested membrane shows more than 80% rejection for Dextran with MW more than 100 kDa, and a partial rejection for Dextran with Mw from 10 kDa to 100 kDa, and a less than 20% rejection for Dextran with MW smaller than 10kDa.
Keywords: ultrafiltration; surface modification; microfiltration; membrane separation; inverse colloidal crystal; ATRP; Membrane separation; Ultrafiltration; Liquid crystal films; Colloidal crystals; Nanostructured materials; Membranes (Technology)